(untitled) (Quinto Sol, 2013)
This paper analyzes fleeting moments in the lives of several minors who were interned in “decent” houses and nunneries, at the disposal of the judiciary, at the beginning of the 20th century in the Río Negro National Territory (Northern Patagonia). The deposit of minors, with a long colonial tradition, is a topic forgotten by Argentine historiography that analyzes the problem of the construction of republican power and the republican State.